Identification of the Kelch family protein Nd1-L as a novel molecular interactor of KRIT1. - Paolo Guazzi; Luca Goitre; Elisa Ferro; Valentina Cutano; Chiara Martino; Lorenza Trabalzini; Saverio Francesco Retta (PLoS ONE)
Loss-of-function mutations of the KRIT1 gene (CCM1) have been associated with the Cerebral Cavernous Malformation (CCM) disease, which is characterized by serious alterations of brain capillary architecture. The KRIT1 protein contains multiple interaction domains and motifs, suggesting that it might act as a scaffold for the assembly of functional protein complexes involved in signaling networks. In previous work, we defined structure-function relationships underlying KRIT1 intramolecular and intermolecular interactions and nucleocytoplasmic shuttling, and found that KRIT1 plays an important role in molecular mechanisms involved in the maintenance of the intracellular Reactive Oxygen Species (ROS) homeostasis to prevent oxidative cellular damage. Here we report the identification of the Kelch family protein Nd1-L as a novel molecular interactor of KRIT1. This interaction was discovered through yeast two-hybrid screening of a mouse embryo cDNA library, and confirmed by pull-down and co-immunoprecipitation assays of recombinant proteins, as well as by co-immunoprecipitation of endogenous proteins in human endothelial cells. Furthermore, using distinct KRIT1 isoforms and mutants, we defined the role of KRIT1 domains in the Nd1-L/KRIT1 interaction. Finally, functional assays showed that Nd1-L may contribute to the regulation of KRIT1 nucleocytoplasmic shuttling and cooperate with KRIT1 in modulating the expression levels of the antioxidant protein SOD2, opening a novel avenue for future mechanistic studies. The identification of Nd1-L as a novel KRIT1 interacting protein provides a novel piece of the molecular puzzle involving KRIT1 and suggests a potential functional cooperation in cellular responses to oxidative stress, thus expanding the framework of molecular complexes and mechanisms that may underlie the pathogenesis of CCM disease.